TRUNCATED PLATONIC SOLID DAN TRUNCATED ICOSIDODECAHEDRON - Maslina Simanjuntak (Universitas Islam Sumatera Utara, 2017)
The background of this paper is to attract society interest to know the beauty of mathematics that is represented by the diversity of mathematics geometry. Truncated Platonic Solid is one of those geometry which is expected to represent the beauty of mathematics. Truncated Platonic solid is a cut off Platonic Solid (not perfect). Platonic Solid is a geometry that was built by congruent polygon, all of the ribs have an equal lenght, also that same surface angle. Truncated Platonic Solid consist of cut off Tetrahedron, cut off Hexahedron, cutt of Dodecahedron, cut off Octahedron, and cutt off Icosahedron. Truncared Icosidodecahedron is a cut off Icosidodecahedron